Do Managers Face a Performance Trade-Off? Correlations Between Production and Process Performance. Issue 1 (1st January 2018) - Mikkelsen, Maria Falk
ABSTRACT: The existence of multiple goals in public organizations inevitably raises the concern that managers face performance trade-offs. In particular, scholars have expressed the fear that public managers, in order to secure high production performance, are forced to sacrifice performance on goals like equity, accountability, and procedural justice. However, our knowledge of whether such trade-offs exist is scarce. Using an administrative 10-year panel data set of Danish public schools and principals, this article analyzes trade-offs between production performance (measured by student performance and student pass rate) and process performance (measured by equity, accountability, and procedural justice). Results show no evidence of trade-offs. In contrast, principals who succeed in raising student performance generally also succeed in securing high pass rates, high equity, high accountability, and high procedural justice. These results suggest that managers who are able to secure high performance on one dimension of performance will likely also be high-performing on other performance dimensions.